The Influence of User Interface, Perceived Ease of Use, and E-Service Quality on User Satisfaction in Using the BRImo Application among Surabaya Residents - Abdul Rochim; Saqofa Nabilah Aini (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of User Interface, Perceived Ease of Use, and E-Service Quality on user satisfaction in using the BRImo application. The research employed a quantitative approach by distributing questionnaires to active BRImo users, and the data were processed using Partial Least Square (PLS) with a total of 120 respondents. The results indicate that all three variables have a positive and significant effect on user satisfaction. These findings suggest that an easily understandable interface, ease of use, and reliable digital service quality can enhance the user experience and satisfaction. This study recommends that BRImo continue to strengthen service stability, improve transaction processing speed, and maintain an intuitive interface design to ensure sustained user satisfaction.